Pendampingan Mahasiswa Klinik Etik dan Advokasi untuk Menjaga Marwah Pengadilan di Indonesia - Musyafa’ah, Nur Lailatul; Rohman, Holilur; Rohman, Moh. Faizur; Solikin, Agus; Ilmiyah, Zainatul; Nooriansyah, Subhan (Proceedings of Annual Conference on Community Engagement, 2022)
Ethics and Advocacy Clinic is a partnership program between the Judicial Commission of the Republic of Indonesia and the Faculty of Sharia and Law at UIN Sunan Ampel Surabaya. The Ethics and Advocacy Clinic activities were held from September 26, 2021, to November 20, 2021, every Saturday from 07.30-09.30 AM via Zoom media. The zoom media was chosen as a follow-up to the ToT held by the Indonesian Judicial Commission with the Mentor of Ethics and Advocacy Clinic in 2021. The Ethics and Advocacy Clinic participants in 2021 are 30 students who have been selected after going through various selections. So that students can take part in the Ethics and Advocacy Clinic (KEA) program and do their work well, mentoring from the lecturers of the Sharia and Law Faculty of UIN Sunan Ampel Surabaya is needed. Assistance is provided from recruitment to implementation and reporting. The mentoring results concluded that mentors play an active role in recruiting, assisting and evaluating KEA activities in 2021. With this assistance, students are responsible for the tasks given. They can carry out tasks according to scheduled activities, including: orientation, opening KEA, writing training in the media, deepening professional material code of ethics and code of ethics for judges, deepening PMKH material and webinars on Revitalizing Public Trust in Law Enforcement to Minimize acts of humiliating the honour of judges (PMKH)”. Mentors always evaluate after the activities are completed. It enables KEA participants to participate in KEA activities well from beginning to end.